PAVING the Path to Wellness for Breast Cancer Survivors: Lifestyle Medicine Education and Group Interventions. Issue 3 (May 2021) - Comander, Amy; Frates, Beth; Tollefson, Michelle
There are over 3.5 million breast cancer survivors living in the United States. Key elements of breast cancer survivorship care include monitoring for disease recurrence, addressing medical and psychosocial consequences of treatment, and educating about lifestyle interventions which decrease risk of recurrence, improve quality of life, and improve outcome. We have developed the PAVING the Path to Wellness Program for Breast Cancer Survivors in order to provide education on evidence-based topics from lifestyle medicine, with the goal to help women adopt healthy habits and improve well-being after cancer treatment. The 12-week program includes all 6 pillars of lifestyle medicine, as well as positive psychology, gratitude, and goal setting work. The PAVING the Path to Wellness Program for Breast Cancer Survivors empowers breast cancer survivors with knowledge regarding evidence-based lifestyle recommendations and helps them achieve an improved sense of well-being following treatment. On completion of the program, participants specifically reported an improvement in attitude and well-being. Next steps involve developing a strategy to offer this program to a larger group of cancer survivors.